Preparation of lithium-mica glass-ceramic containing Cr2O 3 as the machinable insulator - Phumas S. (2014)
The crystallization behavior and electrical properties of lithium-mica glass ceramics materials containing Cr2O3 were investigated as a function of heat treatment condition, i.e. temperature and dwell time. The glass-ceramics samples were produced from the parent glass that prepared via a conventional melt quenching method. The glass specimens were subjected to heat treatment at selected temperatures and times which were determined from DTA measurement. Phase formation was characterized by X-ray diffraction analysis. The results showed that mica phase (Mg 2.5Si4O10)F2 started to form at 650°C but its presence was coupled with formation of Mg2.5Si 4O12 phase. When the treatment temperature was high enough, formation of pure mica phase was obtained. Increasing of the treatment temperature and the dwell time also induced the crystal growths which were revealed by SEM micrographs. Measurement of the electrical conduction and dielectric constant showed that lithium mica glass-ceramic exhibited high electrical resistivity and dielectric stable which are required in the insulator applications. © 2013 Copyright Taylor and Francis Group, LLC.